2014
DOI: 10.1128/mcb.00279-13
|View full text |Cite
|
Sign up to set email alerts
|

Psy2 Targets the PP4 Family Phosphatase Pph3 To Dephosphorylate Mth1 and Repress Glucose Transporter Gene Expression

Abstract: The reversible nature of protein phosphorylation dictates that any protein kinase activity must be counteracted by protein phosphatase activity. How phosphatases target specific phosphoprotein substrates and reverse the action of kinases, however, is poorly understood in a biological context. We address this question by elucidating a novel function of the conserved PP4 family phosphatase Pph3-Psy2, the yeast counterpart of the mammalian PP4c-R3 complex, in the glucose-signaling pathway. Our studies show that P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 39 publications
0
28
0
2
Order By: Relevance
“…Several PP4 targets interact stably with the phosphatase (Keogh et al, 2006; Lee et al, 2010; Ma et al, 2014; O’Neill et al, 2007). Thus, we hypothesized that Pph3 might regulate Mec1, and not only counteract the enzyme by dephosphorylating its targets.…”
Section: Resultsmentioning
confidence: 99%
“…Several PP4 targets interact stably with the phosphatase (Keogh et al, 2006; Lee et al, 2010; Ma et al, 2014; O’Neill et al, 2007). Thus, we hypothesized that Pph3 might regulate Mec1, and not only counteract the enzyme by dephosphorylating its targets.…”
Section: Resultsmentioning
confidence: 99%
“…Protein kinase A (PKA) affects glucose sensing at multiple levels [inhibition of Snf1 (Barrett et al, 2012), Rgt1 (Kim and Johnston, 2006, Roy et al, 2014) and Mth1 (Ma et al, 2014)], and is activated by Mec1 inhibition of the PKA regulatory subunit Bcy1 (Searle et al, 2011). We observed that phosphorylation of Mms21 in response to glucose (but not MMS) is reduced by overexpression of the PDE2 phosphodiesterase ( Figures 1b, c ) and that phosphorylation of Mms21 on a PKA consensus motif ( RxxS, Figure 1e ) is affected by changes in PKA activity.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, yeast R3, Psy2, specifically interacts with the glucose signal transducer protein Mth1 as a prerequisite for the PP4c–R3-mediated dephosphorylation of both Mth1 and a transcriptional repressor, Rgt1 (see ref. 18 ). These studies suggest that R3s are substrate-targeting subunits of PP4 but how substrate specificity is achieved remains unknown.…”
mentioning
confidence: 99%